DeepConcolic: Testing and Debugging Deep Neural Networks - Sun, Youcheng; Huang, Xiaowei; Kroening, Daniel; Sharp, James; Hill, Matthew; Ashmore, Rob (Proceedings (IEEE/ACM International Conference on Software Engineering Companion. Online), 2019)
Deep neural networks (DNNs) have been deployed in a wide range of applications. We introduce a DNN testing and debugging tool, called DeepConcolic, which is able to detect errors with sufficient rigour so as to be applicable to the testing of DNNs in safety-related applications. DeepConcolic is the first tool that implements a concolic testing technique for DNNs, and the first testing tool that provides users with the functionality of investigating particular parts of a DNN. The tool has been made publicly available and a demo video can be found at https://youtu.be/rliynbhoNLM.